Long Term Transmission Expansion Planning considering Generation-Demand Scenarios and HVDC lines - Escobar, Laura Monica [UNESP]; Romero L, Ruben A. [UNESP]; Escobar Z, Antonio H.; Gallego R, Ramon A.; IEEE (Ieee, 2016)
This paper presents a mathematical model and a methodology to solve the transmission expansion planning problem considering generation-demand scenarios and alternative investments using High Voltage Direct Current (HVDC) links. The methodology determines the optimal expansion plan that allows the power system to operate properly in an environment with extreme generation scenarios and multiple demand scenarios obtained for the pessimistic and optimistic scenarios projected. The multiple generation-demand scenarios produced high investment cost for the future network but this cost can be reduced including HVDC links in the expansion alternatives. The planning problem is solved using C++ and CPLEX. The methodology is tested on the modified Garver system with good results.
Keywords: Optimization; HVDC; Transmission Network Expansion Planning; Extreme Generation Scenarios; Demand Scenarios